Efektivitas Pengelolaan Data dan Informasi Kependudukan Melalui Sistem Informasi Data Keluarga (SIGA) (Studi Pada Badan Kependudukan Keluarga Berencana Nasioanal (BKKBN) Provinsi Bengkulu - Milla Anggriani; Harius Eko Saputra; Dahlia Dahlia; Yanuar Rikardo (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effectiveness of population data and information management through the Family Data Information System (SIGA) at BKKBN of Bengkulu Province. This research uses a descriptive method with a qualitative approach. Data collection techniques were conducted through interviews, observations, and documentation with informants directly involved in program implementation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the effectiveness of population data and information management through SIGA can be categorized as fairly effective based on five indicators. On the program success indicator, the implementation of family data updating has proceeded according to the established stages although there are still technical obstacles such as network and server disruptions. On the target achievement indicator, the data collection targets have generally been met, but not evenly across all regions. From the satisfaction aspect, the SIGA system is considered to facilitate the process of recording and reporting family data. On the input and output indicators, support from human resources and technological systems has produced integrated family data. Overall, the program's objective of providing accurate and integrated population data has been achieved, although improvements are still needed in the aspects of infrastructure and human resource capacity.